2019
DOI: 10.12688/f1000research.20174.1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of viral hepatitis B and C in Punjab, Pakistan: a multicenter cross-sectional study, 2017-18

Abstract: Background: Globally, approximately 240 million people are chronically infected with hepatitis B virus (HBV) and hepatitis C virus (HCV), which are responsible for 96% of all hepatitis-related mortality. Pakistan has the second highest prevalence of HCV in the world. Methods: We conducted this study to ascertain the prevalence and potential risk factors associated with HBV and HCV infections in Punjab. A multi-center cross-sectional study was conducted, involving 24 Hepatitis Prevention and Treatment Clinics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
4
16
0
2
Order By: Relevance
“…The results when compared with a similar study[ 13 ] conducted in the general population of Pakistan almost correlated with young patients of up to 40 years. However, when comparing with a second study published in 2019 at an outreach center for screening and treatment in Pakistan,[ 14 ] it was found that most older age people (>61 years) were positive. It may be due to the inability of patients to seek medical attention after appearing of symptoms due to various reasons like finances, etc., eventually seeking medical help at a later stage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results when compared with a similar study[ 13 ] conducted in the general population of Pakistan almost correlated with young patients of up to 40 years. However, when comparing with a second study published in 2019 at an outreach center for screening and treatment in Pakistan,[ 14 ] it was found that most older age people (>61 years) were positive. It may be due to the inability of patients to seek medical attention after appearing of symptoms due to various reasons like finances, etc., eventually seeking medical help at a later stage.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, gender trends similar to our study were observed in another study that indicated women being infected more at a ratio of 1:3. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients with positive and negative HBsAg was 48.7 ± 17.6 and 45.9 ± 21.22, respectively, and the difference was statistically significant. Studies report a strong relationship between age and HBsAg positivity (18,19). Nonetheless, a significant variation exists between regions and countries regarding the relationship of age groups with HBsAg positivity.…”
Section: Discussionmentioning
confidence: 99%
“…In every province, there are more than 28 districts which have a higher prevalence of hepatitis B. 9 This study aimed to assess the knowledge, attitude and practices of dental practitioners against Hepatitis B in district Faisalabad.…”
Section: Correspondencementioning
confidence: 99%